2020
DOI: 10.1088/1748-9326/ab751f
|View full text |Cite
|
Sign up to set email alerts
|

Increased population exposure to precipitation extremes under future warmer climates

Abstract: Precipitation extremes are among the most dangerous climate-related hazards, and these hazards often cause large socioeconomic losses and exert severe human health impacts each year. It is thus crucial to assess future exposure changes to precipitation extremes under different warming scenarios to improve the mitigation of climate change. Here, we project future exposure using a set of Coupled Earth System Model low-warming simulations and RCP8.5 large ensemble simulations. We find that the precipitation extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 42 publications
2
38
0
1
Order By: Relevance
“…al., 2016). With continuous rapid warming expected in the future, increases are expected to be much larger than the current climates across the world (e.g., Zhou et al, 2014;Chen et al, 2020a); this is also validated by the results of the latest CMIP6 models (Figure 1). In response to future warming, the ensemble mean of the CMIP6 models presents a consistent increasing trend of days of precipitation extreme averaged over global lands, but it varies among the scenarios.…”
Section: Accepted Articlesupporting
confidence: 55%
See 2 more Smart Citations
“…al., 2016). With continuous rapid warming expected in the future, increases are expected to be much larger than the current climates across the world (e.g., Zhou et al, 2014;Chen et al, 2020a); this is also validated by the results of the latest CMIP6 models (Figure 1). In response to future warming, the ensemble mean of the CMIP6 models presents a consistent increasing trend of days of precipitation extreme averaged over global lands, but it varies among the scenarios.…”
Section: Accepted Articlesupporting
confidence: 55%
“…Recent studies have shown that global aggregate exposure to precipitation extremes is projected to increase in the future (Liao et al, 2019;Chen et al, 2020a), by approximately 2.3% if the temperature increases by 2.0 o C relative to the pre-industry era rather than by 1.5 o C calculated from the CESM simulations (Chen et al, 2020a).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The focus of this study is on the long-term changes and characteristics of extreme daily precipitation on a global scale rather than on the characteristics or impacts of a handful single events. Therefore, we use the daily precipitation from CESM as it is in the next section, i.e., without applying any further corrections, such as bias correction (e.g., Chen et al, 2020) or downscaling methods (e.g., Yang et al, 2012). Still, we take into account the differences between ERA5 and CESM in the magnitudes of extreme precipitation when interpreting our results and discussing possible implications in the conclusions.…”
Section: Statistical Tests Used For the Model Evaluation Against Era5mentioning
confidence: 99%
“…The overall damage and costs directly linked with extreme events between 1997 and 2016 reached about $3.16 trillion (Eckstein et al ., 2017). Without effective progress in reducing greenhouse gas emissions, the frequency and intensity of extreme weather/climate events and the losses induced by these events are expected to rapidly increase in the 21st century (IPCC, 2012; Chen et al ., 2020). For example, the global gross domestic product (GDP) might reduce sharply by >30% for a 4°C increase in global warming (Burke et al ., 2018), greater than the reduction in the Great Depression when global trade fell by 25%.…”
Section: Introductionmentioning
confidence: 99%